PENGARUH UKURAN PERUSAHAAN, CURRENT RATIO, DEBT TO EQUITY RATIO, DAN RETURN ON ASSETS TERHADAP NILAI PERUSAHAAN - Louis Louis; Anissa Amalia Mulya (CV. Denasya Smart Publisher, 2025)
This study aims to examine the effect of Company Size, Current Ratio, Debt to Equity Ratio, and Return on Assets on Firm Value. Company Size, Current Ratio, Debt to Equity Ratio, and Return on Assets serve as independent variables, while Firm Value serves as the dependent variable. This study uses secondary data from a population of 25 companies, namely Infrastructure companies in the Construction sub-sector listed on the Indonesia Stock Exchange in 2021-2024. A total of 21 (twenty-one) companies were sampled for the study, with observation periods of 2021-2024. The sampling technique used was purposive sampling with multiple linear regression analysis. The results of this study indicate that Company Size, Current Ratio, Debt to Equity Ratio, and Return on Assets partially and simultaneously influence Firm Value.